A Study on Photoneutrons Generated in a Linear Accelerator Head using GEANT4 - Ko, Junho; ang Kim, Yoon S; ., . (International Journal of Engineering and Technology, 2018)
Medical linear accelerators use high energy for treatment of deeply located tumors. However, linear accelerators using energy above 6 MeV are likely to cause photoneutron contamination. In this paper, we analyzed photoneutrons generated in a linear accelerator head using GEANT4 (GEometry ANd Tracking) simulation. From the simulation results, it was confirmed that the generation of photoneutrons increases in the linear accelerator head as higher the energy of the electron beam.Â Â